2018
DOI: 10.3399/bjgp18x695033
|View full text |Cite
|
Sign up to set email alerts
|

Reducing inappropriate antibiotic prescribing for children in primary care: a cluster randomised controlled trial of two interventions

Abstract: Systematic POC CRP testing without guidance is not an effective strategy to reduce antibiotic prescribing for non-severe acute infections in children in primary care. Eliciting parental concern and providing a safety net without POC CRP testing conversely increased antibiotic prescribing. FPs possibly need more training in handling parental concern without inappropriately prescribing antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 21 publications
0
59
0
Order By: Relevance
“…There were nine cluster random control trials, [15][16][17]19,21,[23][24][25]29 two matched-pair cluster-randomized trials, 26,27 two RCTs, 22,31 two before and after intervention studies, 20,28 one quasi-experimental trial 30 and one interrupted time series study. 18…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were nine cluster random control trials, [15][16][17]19,21,[23][24][25]29 two matched-pair cluster-randomized trials, 26,27 two RCTs, 22,31 two before and after intervention studies, 20,28 one quasi-experimental trial 30 and one interrupted time series study. 18…”
Section: Methodsmentioning
confidence: 99%
“…Of the 17 studies, ten were conducted in Europe, [15][16][17][18][19][20][21][22][23][24] four in China, [25][26][27][28] three in the USA. [29][30][31] Table 1 provides a summary of the key characteristics of each included study.…”
Section: Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Based on the study by Lemiengre and colleagues, use of CRP to guide antibiotic prescribing decisions for children cannot be recommended either. 1 The only study that showed an effect of physician use of CRP in children was a large multicentre RCT in 10 primary healthcare centres in Vietnam. It recruited over 1000 children, and reduced antibiotic prescribing from 77% to 68% in children with acute infections.…”
Section: The Impact Of Crp On Antibiotic Prescribing Decisionsmentioning
confidence: 99%
“…1 They were randomised to a brief intervention that elicited and attempted to address parent concerns, GP use of a CRP test, both, or usual care. The brief intervention paradoxically increased antibiotic prescribing, while GP use of CRP alone or GP use of CRP plus the brief intervention had no significant effect on prescribing.…”
mentioning
confidence: 99%